Percepções de micro e pequenos empresários de Sananduva-RS quanto ao uso de ferramentas gerenciais providas pela contabilidade - Brunetto, Tauane (2022)
The accounting of companies, in addition to serving the Tax Authorities, is a provider of information to managers who, through managerial artifacts, plan, budget, control and assess the situation of the entity. In the Brazilian context, there is an expressive number of Micro and Small companies, and these have considerable mortality rates in their initial years, one of the reasons being the lack of accounting basis for the management of the enterprise. Given this, the objective of this work is to evaluate the perceptions of micro and small entrepreneurs in the retail sector of Sananduva in the state of Rio Grande do Sul regarding the management tools provided by accounting. This is a quantitative research, a survey, with the participation of 10 businessmen from the Sananduvense retail trade sector, who answered a closed questionnaire, where their perception of the importance of using tools was verified. The survey identified that entrepreneurs rely more on their intuition/experience than on accounting reports for decision making. That is, business managers are aware of the accounting relevance in the management process, but they trust more in their experiences as owners of the organization, not changing their habits, so micro and small entrepreneurs can be encouraged to use the tools identified in this research. and the other existing tools, through academic specializations, by promoting events aimed at this class, or even the accountant, who has greater contact, trying to inform them about the need for use.